HARMONISATION OF DOMESTIC LEGISLATION IN THE FIELD OF CIVIL LAW WITH THE EUROPEAN UNION LAW – SECURING OF CLAIMS BY MEANS OF FIDUCIARY AGREEMENTS - Pajtić, Bojan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
This paper analyses fiduciary agreements, which, as a form of contract, that is the means of securing obligation and legal claims, are regulated by provisions of specific laws and codifications in some of the European Union countries. Even the Montenegrin legislator enacted a special law governing these legal matters, however in the Serbian law fiduciary agreements fall into the category of innominate contracts. Fiducia originates in the Roman Law and constitutes the first common form of the pledge law. The Latin term fiducia means „trust“, since these legal matters were, first of all, based on the trust between contractual parties. This paper addresses the institution of ’’trust’’ as it is the Anglo-Saxon counterpart of the fiduciary agreement. Etymologically, ’’trust’’ has the same meaning as the term fiducia - trust. Due to their advantages, fiduciary agreements are not even uncommon in the domestic legal practice, while there are certain, as we have already announced, theoretical, but also practical concerns arguing admissibility of this legal matter. These arguments mainly come down to the thesis (mentioned above) that entering into the fiduciary agreement results in violation of the ban on performance of contract lex commissoria in the pledge law. Nevertheless, I provided explanation that differences between contracts of pledge and fiduciary agreements clearly point to the conclusion that fiduciary agreements may not be treated as a pledge, hence they are admissible, that is, they are concluded on the principle of contractual freedom as an imperative norm of the Law on Obligations. Fiduciary agreements (in relation to the realistic means of security) offer to the creditor a higher level of security, reduce the period of payment of his claims, also providing practical benefits for the debtor himself. The paper presents the reasons supporting the view that it would be advantageous for the Serbian legislator, in the process of harmonisation of the legislation in the field of Civil Law with the European Union law, to regulate the institute of fiduciary agreements under the special law, integrate it into the Law on Obligations or make it a part of the future Civil Code of the Republic of Serbia.